Elaboração e análise de indicadores bibliométricos de publicações na área de educação em engenharia de materiais - Almeida Filho, Humberto Dias de (2021)
Engineering is directly related to the industrial and socioeconomic development of each country and region in which it operates, being a central area in its development. Indispensable to the present day, the engineering professional, whose reflection of his work directly implies changes in society must present a generalist, critical, humanistic and reflective profile. With the demand for new skills from new professionals, such as: leadership, entrepreneurship and innovation, efforts are being made worldwide in an attempt to modernize engineering curricula, thus increasing the importance of the field of research in engineering education, including materials engineering education. This work proposed to carry out an analysis of data from the application of bibliometric techniques, in records retrieved in the “Web of Science” platform. The search in the database was directed to the area “Education in Materials Engineering” and, after processing the data collected, the identification of the main countries; possible research groups, institutions, as well as possible trends related to the theme were made. After analyzing the data, it was possible to verify the US hegemony in research in education in materials engineering through the number of publications, main institutions and authors. Brazil, in turn, is in 4th position in overall number of publications, accounting for 4.5% of total publications. It is also worth mentioning the presence of a Brazilian researcher as the main author on the topic. Recently implemented public policies can act positively for greater growth in Brazil in such a scenario.